Relationship Between Knowledge, Attitude, and Family Support with Exclusive Breastfeeding - Sukarni; Nani Surtinah; Budi Joko Santoso; Agung Suharto (Forum Ilmiah Teknologi dan Ilmu Kesehatan (FORITIKES), 2024)
The effort to improve the quality of human resources (HR) begins from infancy in the womb. One of the efforts to ensure a well-growing and developing baby is by providing Exclusive Breastfeeding (EBF). Globally, the provision of EBF is lower than needed. This study aims to determine the relationship between knowledge, attitude, and family support towards the provision of exclusive breastfeeding in the working area of UPTD Puskesmas Plaosan Magetan. Method : This research is an analytical survey study with a cross-sectional design. The research sample was taken using Simple Random sampling technique, amounting to 37 mothers with infants aged 0-6 months. The independent variables are knowledge, attitude, and family support, and the dependent variable is the provision of Exclusive Breastfeeding. Data collection was conducted using questionnaires and baby register books. To analyze the relationship between knowledge, attitude, and family support, Bivariate analysis was used, and the tests used were chi-square or fisher exact tests. Result : The results showed that there was no relationship between knowledge and the provision of Exclusive Breastfeeding (p-value = 0.447), there was a relationship between attitude and the provision of Exclusive Breastfeeding (p-value = 0.005), and there was a relationship between family support and the provision of Exclusive Breastfeeding (p-value = 0.002). Discussion : Based on the results of the study, it is concluded that the success of Exclusive Breastfeeding is related to attitude and family support; however, attitude and family support are formed from good knowledge and a positive mindset. Suggestion : Therefore, it is recommended for UPTD Puskesmas Plaosan to develop educational programs involving family participation and community leaders, as well as to improve health services.